A framework for cultural heritage content organisation, dissemination and communication in large-scale virtual environments. (2016) - Komianos, Vasileios; Tsoumanis, Georgios; Kavvadia, Eleni; Oikonomou, Konstantinos
Cultural heritage promotion is an emerging trend for cultural organisations which take advantage of informatics and virtual environments for this purpose. Virtual environments are an effective media for cultural content communication combining existing communication media and providing diverse interaction methods. In this paper, these methods are tested for their effectiveness and appropriateness under certain conditions while usability issues are addressed. In many cases, there is demand for the content to be organised and be available to other systems. Virtual environments do not provide content organisation and content dissemination functionality, thus, a framework providing them is proposed. A database (RDBMS) is used for keeping the content according to an appropriately designed information schema that further organises it. Dissemination requirements are taken into consideration and add-on mechanisms are designed to provide access to the content and dissemination services adapted to the modern World Wide Web technologies.